Differences in Working Memory With Emotional Distraction Between Proficient and Non-proficient Bilinguals - Ma, Xie; Ma, Xiao; Li, Peng; Liu, Yan (Frontiers in Psychology, 2020)
The impact of bilingual education and bilingual experience on working memory has been an important and controversial issue in the field of psycholinguistics. Taking Chinese-English bilinguals as an example, this study aims to investigate the differences in emotional working memory between proficient and non-proficient bilinguals by using delayed matching-to-sample task paradigm and more complex n-back task in the context of emotion. The results show that proficient bilinguals have better performance on both of the two working memory tasks than non-proficient bilinguals, and the advantage effects were more apparent under high memory load conditions. Besides, the negative emotion context has a positive impact on complex n-back tasks. This study supports the notion that bilingual experience can promote the development of an individual’s cognitive ability and enable individuals to possess more advantages in working memory even in the presence of emotional distractions.